2005
DOI: 10.1007/s10681-005-1742-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification, distribution and effects on agronomic traits of the semi-dwarfing Rht alleles in Bulgarian common wheat cultivars

Abstract: Bulgarian common wheat cultivars released in the period 1925-2003 were studied using the gibberellic acid (GA) test and microsatellite analysis of the Xgwm261 locus on chromosome 2DS to identify the semi-dwarfing (Rht) genes. The old cultivars, isolated through selection from landraces, carried rare alleles (211-and 215-bp) at Xgwm261 locus, and those developed by hybridisation to foreign cultivars, carried the 165-and 174-bp alleles. Forty-two (55.3%) of 76 modern cultivars were GA-responsive. The 192-bp alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 22 publications
(35 reference statements)
2
41
2
Order By: Relevance
“…Winter wheat varieties from Central European countries exerted the main negative effect on this correlation. Pobeda, the only variety out of 14 Central European varieties was investigated for Rht genes and possessed Rht8 [21]. No evidence on the rest of the varieties was found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Winter wheat varieties from Central European countries exerted the main negative effect on this correlation. Pobeda, the only variety out of 14 Central European varieties was investigated for Rht genes and possessed Rht8 [21]. No evidence on the rest of the varieties was found.…”
Section: Discussionmentioning
confidence: 99%
“…However, involvement of exotic germplasm with a complex of undesirable agronomic traits can impede breeding. Many Southern and Central European varieties possess Rht8 alone or in combinations with Rht-D1 or Rht-B1 [5,21]. Probably, some of them possess long coleoptiles.…”
Section: Introductionmentioning
confidence: 99%
“…Wheat genotypes with only one copy allele are photoperiod-sensitive whereas an increased copy number (2-4 copies) results in a day-neutral, early flowering phenotype. A complementary study [100] confirmed that wheat genotypes with the three-copy allele (termed Ppd-B1a) and the four-copy allele (termed Ppd-B1c) exhibit reduced days to heading as compared to the onecopy allele (termed Ppd-B1b) whereas the two-copy allele (termed Ppd-B1d) displays increased days to heading (late flowering). These results indicate that the CNV at the Ppd-B1 locus contributes in fine-tuning the adaptation of wheat to local climatic conditions, in addition to the major effect of Ppd-D1.…”
Section: The Role Of Diagnostic Molecular Markers In the Detection Ofmentioning
confidence: 89%
“…Therefore, breeding for wheat cultivars with flexible response in different environments and that exhibit superior performance under extreme conditions, such as hot and dry environments, should become a priority. Photoperiod insensitivity is usually an advantage in most regions [100]. Therefore, selecting for the trait and incorporating genes for other complementary traits, such as preharvest sprouting resistance into the advanced lines, could be an added advantage in addition to significant yield improvement.…”
Section: Concluding Remarks and Future Breeding Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation